2019
DOI: 10.5194/acp-19-15569-2019
|View full text |Cite
|
Sign up to set email alerts
|

Multi-method determination of the below-cloud wet scavenging coefficients of aerosols in Beijing, China

Abstract: Abstract. Wet scavenging is one of the most efficient processes for removing aerosols from the atmosphere. This process is not well constrained in chemical transport models (CTMs) due to a paucity of localized parameterization regarding the below-cloud wet scavenging coefficient (BWSC). Here we conducted field measurements of the BWSC during the Atmospheric Pollution and Human Health Beijing (APHH-Beijing) campaign of 2016. Notably, the observed BWSC values based on the updated aerosol mass balance agree well … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 56 publications
4
46
0
Order By: Relevance
“…The measurement site is located on the roof of a two-floor building at the Institute of Atmospheric Physics tower site (IAP-tower; 39 • 58 28 N, 116 • 22 1 E) in northern Beijing. It is a typical urban site between the 3rd and 4th ring roads and lying close to the Badaling expressway (Xu et al, 2017(Xu et al, , 2019Sun et al, 2015). Four years of inter-annual observations of each rainfall event were conducted at this site.…”
Section: Measurement Site and Sampling Methodologymentioning
confidence: 99%
See 4 more Smart Citations
“…The measurement site is located on the roof of a two-floor building at the Institute of Atmospheric Physics tower site (IAP-tower; 39 • 58 28 N, 116 • 22 1 E) in northern Beijing. It is a typical urban site between the 3rd and 4th ring roads and lying close to the Badaling expressway (Xu et al, 2017(Xu et al, , 2019Sun et al, 2015). Four years of inter-annual observations of each rainfall event were conducted at this site.…”
Section: Measurement Site and Sampling Methodologymentioning
confidence: 99%
“…However, more recent extensive research on wet scavenging has found that precipitation, even light rain, can remove 50 %-80 % of the number or mass concentration of belowcloud aerosols, and this is supported by both field measurements and semi-empirical parameterizations of below-cloud scavenging in models (Andronache, 2004b;Zhang et al, 2004;Wang et al, 2014). Xu et al (2017Xu et al ( , 2019 studied the below-cloud scavenging mechanism based on the simultaneous measurement of aerosol components in rainfall and in the air in Beijing. They found that below-cloud scavenging coefficients for PM 2.5 widely used in CTMs (∼ 10 −5 -10 −6 ) were 1-2 orders of magnitude lower than estimates from observations (at the range of 10 −4 -10 −5 for SO 2− 4 , NO − 3 , and NH + 4 .).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations